Progress and Performance of States in Promotion of Farmer Producer Organisations in India - Manaswi B.H., Pramod Kumar, Prakash P., P. Anbukkani, Amit Kar, G.K. Jha; D.U.M. Rao (Indian Journal of Extension Education, 2018)
There has been a substantial increase in the performance of Farmers Producer Organizations (FPOs). However, the growth of FPOs across the states and regions in India has not been uniform. Therefore, an in-depth analysis was taken up (a) to examine the status and growth of Farmer Producer Organizations across states and regions in India, and (b) to examine the performance of Farmer Producer Organizations and to suggest measures to improve it. The study used discriminant function analysis to examine the factors influencing the performance of states. The findings indicated that more than 50% of total mobilised farmers belonging to four states namely Karnataka, Madhya Pradesh, Tamil Nadu and West Bengal. The highest number of promoting institutions have found in Karnataka (85) constituting about 8.9 % of the total promoting agencies functioning in the country. The number of FPOs promoting institutions per gross cropped area, ease of doing business, number of markets, KCC per operational holding and rural literacy are significant factors having bearing on the performance of the states.